Adjunct n-3 Long-Chain Polyunsaturated Fatty Acid Treatment in Tuberculosis Reduces Inflammation and Improves Anemia of Infection More in C3HeB/FeJ Mice With Low n-3 Fatty Acid Status Than Sufficient n-3 Fatty Acid Status - Hayford, Frank E. A.; Dolman, Robin C.; Ozturk, Mumin; Nienaber, Arista; Ricci, Cristian; Loots, Du Toit; Brombacher, Frank; Blaauw, Renée; Smuts, Cornelius M.; Parihar, Suraj P.; Malan, Linda (Frontiers in Nutrition, 2021)
Populations at risk for tuberculosis (TB) may have a low n-3 polyunsaturated fatty acid (PUFA) status. Our research previously showed that post-infection supplementation of n-3 long-chain PUFA (LCPUFA) in TB without TB medication was beneficial in n-3 PUFA sufficient but not in low-status C3HeB/FeJ mice. In this study, we investigated the effect of n-3 LCPUFA adjunct to TB medication in TB mice with a low compared to a sufficient n-3 PUFA status. Mice were conditioned on an n-3 PUFA-deficient (n-3FAD) or n-3 PUFA-sufficient (n-3FAS) diet for 6 weeks before TB infection. Post-infection at 2 weeks, both groups were switched to an n-3 LCPUFA [eicosapentaenoic acid (EPA)/docosahexaenoic acid (DHA)] supplemented diet and euthanized at 4- and 14- days post-treatment. Iron and anemia status, bacterial loads, lung pathology, lung cytokines/chemokines, and lung lipid mediators were measured. Following 14 days of treatment, hemoglobin (Hb) was higher in the n-3FAD than the untreated n-3FAS group (p = 0.022), whereas the n-3FAS (drug) treated control and n-3FAS groups were not. Pro-inflammatory lung cytokines; interleukin-6 (IL-6) (p = 0.011), IL-1α (p = 0.039), MCP1 (p = 0.003), MIP1- α (p = 0.043), and RANTES (p = 0.034); were lower, and the anti-inflammatory cytokine IL-4 (p = 0.002) and growth factor GMCSF (p = 0.007) were higher in the n-3FAD compared with the n-3FAS mice after 14 days. These results suggest that n-3 LCPUFA therapy in TB-infected mice, in combination with TB medication, may improve anemia of infection more in low n-3 fatty acid status than sufficient status mice. Furthermore, the low n-3 fatty acid status TB mice supplemented with n-3 LCPUFA showed comparatively lower cytokine-mediated inflammation despite presenting with lower pro-resolving lipid mediators.